Comparison of immune resilience induced by vaccination versus COVID recovery - Landau, Ned (Henry Stewart Talks, 2021)
The need to characterize vaccine-indued immunity in more detail, Methods for comparison of convalescent versus vaccination-induced plasma, Higher effectiveness of antibodies induced by mRNA vaccination, Characteristics of the new lambda variant – implications for immune escape, Mechanisms leading to the increased efficiency of vaccine-induced antibodies compared to those of recovered patients.